FoxP3 in Treg cell biology: a molecular and structural perspective. (3rd September 2019) - Deng, G.; Song, X.; Greene, M. I.
Summary: Regulatory T cells (Tregs ) are specialized in immune suppression and play a dominant role in peripheral immune tolerance. Treg cell lineage development and function maintenance is determined by the forkhead box protein 3 (FoxP3) transcriptional factor, whose activity is fine‐tuned by its post‐translational modifications (PTMs) and interaction partners. In this review, we summarize current studies in the crystal structures, the PTMs and interaction partners of FoxP3 protein, and discuss how these insights may provide a roadmap for new approaches to modulate Treg suppression, and new therapies to enhance immune tolerance in autoimmune diseases. Abstract : FOXP3 is the master transcription factor in regulating Treg cell development and function. The forkhead domain of FOXP3 forms a domain‐swapped dimer which can bridge two long‐range FOXP3‐targeted genes (a). The zinc‐finger and leucine‐zipper domain forms oligomerization through the hydrophobic coiled‐coil surface (b). Acetylation of K250 and K252 located in the coiled‐coil region changes the conformation of FOXP3, which implies a structure‐based regulation of the conformation and activity of FOXP3 by integration of posttranslational modifications may modulate Treg function. Understanding the molecular and structural features of Foxp3 helps to design rational therapeutic strategies against autoimmune diseases.